Governance and Developing Asia: Concepts, Measurements, Determinants, and Paradoxes - M.G. Quibria (Asian Development Bank (ADB), 2014)
Recent years have seen the emergence of a considerable volume of literature on governance and its role in economic and social development of a country. This paper provides a critical review of the literature. This review brings into the open a number of serious conceptual, measurement, and data issues as well as the existence of an Asian governance paradox - i.e., a general disjunction between growth and governance in most Asian economies. This paradox seems to suggest that much of the current policy discussion on governance is essentially faith-based. It calls into question the quality of the existing data and the analytical basis of the policy orthodoxy.
hdl:11540/4205
Keywords: O40; O43; P30; P48; 330; government quality; corruption; bureaucracy; social capital